Enhanced Catalyst Activity of WO3 Using Polypyrrole as Support for Acidic Esterification of Glycerol with Acetic Acid - Khadijeh Beigom Ghoreishi; Mohd Ambar Yarmo; Norasikin Mohamad Nordin; Mohd Wahid Samsudin (Journal of Chemistry)
A series of polypyrrole supported WO3 were fabricated and characterized by FT-IR, XRD, XPS, BET, TGA, and FESEM-EDX. The activity of the catalysts was tested in glycerol esterification with acetic acid, and it found that WO3-Ppy-20 (nanocomposite with 20% WO3 loaded) showed the maximum catalyst activity with 98% and selectivity of 70% to triacetin at 110°C with a reaction duration of 10 h and also recorded the highest selectivity (75%) for acetylation of glycerol to monoacetin with about 59% conversion only. The highest acidity of WO3-Ppy-20 is also confirmed using TPD-NH3 analysis. The activity and selectivity to triacetin of the catalyst were enhanced by increasing WO3 loading amount, resulting in 82% conversion for WO3-Ppy-5 with about 32 and 50% selectivity to monoacetin and diacetin and about 18% selectivity to triacetin; in case of WO3-Ppy-20, these amounts were changed to 5, 25, and 70% selectivity to monoacetin, diacetin, and triacetin, respectively with the conversion of 98%. TPD-NH3 analysis found that polypyrrole supported WO3 increases the catalyst acidity of WO3. BET and FESEM analyses revealed that WO3 particles were well dispersed with the smallest average size in nanocomposite compared to pure WO3, which could contribute to the high activity of WO3-Ppy catalyst for esterification of glycerol.